Potential for integrating mental health specialist video consultations in office-based routine primary care: cross-sectional qualitative study among family physicians - Hoffmann, Mariell; Hartmann, Mechthild; Wensing, Michel; Friederich, Hans-Christoph; Haun, Markus W. (Journal of medical internet research)
Background: Although real-time mental health specialist video consultations have been proposed as an effective care model for treating patients with mental health conditions in primary care, little is known about their integration into routine practice from the perspective of family physicians. Objective: This study aimed to determine the degree to which family physicians advocate that mental health specialist video consultations can be integrated into routine primary care, where most patients with mental health conditions receive treatment. Methods: In a cross-sectional qualitative study, we conducted 4 semistructured focus groups and 3 telephonic interviews in a sample of 19 family physicians from urban and rural districts. We conducted a qualitative content analysis applying the Tailored Implementation in Chronic Diseases framework in a combined bottom-up (data-driven) and top-down strategy for deriving key domains. Results: Family physicians indicated that mental health specialist video consultations are a promising and practical way to address the most pressing challenges in current practice, that is, to increase the accessibility and co-ordination of specialized care. Individual health professional factors were the most frequently discussed topics. Specifically, family physicians valued the anticipated clinical outcomes for patients and the anticipated resources set for the primary care practice as major facilitators (16/19, 84%). However, family physicians raised a concern regarding a lack of facial expressions and physical interaction (19/19, 100%), especially in emergency situations. Therefore, most family physicians considered a viable emergency plan for mental health specialist video consultations that clearly delineates the responsibilities and tasks of both family physicians and mental health specialists to be essential (11/19, 58%). Social, political, and legal factors, as well as guideline factors, were hardly discussed as prerequisites for individual family physicians to integrate mental health specialist video consultations into routine care. To facilitate the implementation of future mental health specialist video consultation models, we compiled a checklist of recommendations that covers (1) buy-in from practices (eg, emphasizing logistical and psychological relief for the practice), (2) the engagement of patients (eg, establishing a trusted patient-provider relationship), (3) the setup and conduct of consultations (eg, reliable emergency plans), and (4) the fostering of collaboration between family physicians and mental health specialists (eg, kick-off meetings to build trust). Conclusions: By leveraging the primary care practice as a familiar environment for patients, mental health specialist video consultations provide timely specialist support and potentially lead to benefits for patients and more efficient processes of care. Integration should account for the determinants of practice as described by the family physicians. Trial Registration: German Clinical Trials Register DRKS00012487; https://www.drks.de/drks_web/navigate.do? navigationId=trial.HTML&TRIAL_ID=DRKS00012487 [J Med Internet Res 2019;21(8):e13382]